New Strategies and Approaches for Public Relations in Public Institutions: Theoretical Research - Awaz Hassan Ismail; Lana Sabir Saeed; Azad Ahmad Mahmood (QALAAI ZANIST JOURNAL, 2024)
This paper entitled (New Strategies and Approaches for Public Relations in Public Institutions) it is theoretical research discusses the functions and objectives of public relations in public institutions. Thus, the nature of public relations has led to major changes in all international, regional, and local newspapers; This affects the processes of relations in general but reflects on all the environments of human life. So, if the nature and functions of relationships are positive or negative, its influence on changing relations, positively or negatively, and in its introduction to the media, to translate them into reality. Therefore, the role of public relations at all stages is a sensitive task; all direct and indirect errors affect them; character in the field of public relations; which diagnoses weaknesses and defects and determines treatment tools in a scientific manner; For this purpose, a minute picture of the study of public relations in public institutions through the academic authority. The aim of this research is to provide strategic knowledge and action on the duties and objectives of public relations in the public sector, alongside knowledge of the styles and tools followed in communications; Please know the tools used in your contacts. One of the most important results achieved by the researcher in his research is to strengthen relations between institutions and the public, and also the existence of a strong strategy in public institutions that helps to strengthen the relationship between the institution and the public, and must create new opinions and trends in public institutions through the use of new methods and tools in order to work and achieve the main goals. The method of research is a theoretical method, so the researcher used this method because it fits with the nature of the subject, and through this method, analyzing the subjects.